Analysis of Purbaya’s Economic Policy and Indonesia’s Economic Growth Prospects Towards 6% - Jan Horas Veryady Purba (Westscience Press, 2026)
This study analyzes the effectiveness of economic policies led by Purbaya in maintaining financial system stability and their contribution to achieving Indonesia’s economic growth target of 6 percent. Using a qualitative approach based on policy analysis and macroeconomic data, the study also employs word cloud techniques to identify dominant keywords in policy documents and Purbaya’s economic narratives. The research evaluates the foundations of structural policies, fiscal–monetary synergy, and the readiness of strategic sectors as engines of growth. The findings suggest that achieving 6 percent growth requires a consistent policy mix, improvements in labor productivity, accelerated regulatory reforms, and strengthened domestic and foreign investment. In addition, the study highlights external and domestic risks that may hinder target achievement, including global uncertainty, financial market volatility, and structural challenges in the MSME sector. These findings provide a comprehensive overview of opportunities and obstacles in realizing sustainable economic growth, while offering policy recommendations to enhance national economic resilience.